Experimental results on antiproton–nuclei annihilation cross section at very low energies - Aghai-Khozani H. (EPJ Web of Conferences, 2014)
Investigating the antiproton cross section on nuclei at low energies (1 eV – 1 MeV) is of great interest for fundamental cosmology and nuclear physics as well. The process is of great relevance for the models which try to explain the matter/antimatter asymmetry in the universe assuming the existence of the so-called “island” where antinucleon-nucleon annihilations occur in the border region [1]. For the nuclear physics point of view, the annihilation process is considered a useful tool to evaluate the neutron/proton ratio probing the external region of the nucleus. Moreover, the cross section measured at LEAR in the 80s–90s showed an unexpected behaviour for energies below 1 MeV. The results showed a saturation with the atomic mass number against the A2/3 trend which is known for higher energies. The ASACUSA collaboration at CERN measured 5.3 MeV antiproton annihilation cross section on different nuclei whose results demonstrated to be consistent with the black-disk model with the Coulomb correction [2]. So far, experimental limits prevented the data acquisition for energies below 1 MeV. In 2012 the 100 keV region has been investigated for the first time [3]. We present here the results of the experiment.